Transformation of Zakat and Waqf in Society 5.0: Improving Welfare through the Utilisation of Technology and Social Innovation - Khoerulloh, Abd. Kholik; Sharin, Farah Hida (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2025)
The involvement of technology in the Society 5.0 era has changed the paradigm in the management of social funds such as zakat and waqf. The research aims to explore the potential use of technology and how social innovation can expand its impact on improving the welfare of the people. This study uses a literature study method with a qualitative approach. Data was obtained from a variety of credible literature sources, including academic journals, scientific articles, books, official reports, and materials from related conferences and seminars. An in-depth analysis of this literature is carried out to understand the evolution of the role of zakat and waqf in the context of history, recent developments, and changes with the emergence of Society 5.0. The results of the literature analysis show that the use of technology, such as digital platforms and technology-based financial systems, provides a great opportunity in improving the efficiency of collecting, managing, and distributing zakat and waqf funds. In addition, social innovation also plays an important role in expanding the impact of these philanthropic practices on people's welfare. This research is expected to provide an in-depth understanding of the need to adapt zakat and waqf to the concept of Society 5.0, as well as the importance of public awareness and education on the benefits of zakat and waqf in supporting wider welfare.